How early is early…? The Role of Abdominal Reoperation Predictive Index at dr. Cipto Mangunkusumo General Hospital, Jakarta - Marbun, Vania MG; Lalisang, Toar JM (The New Ropanasuri Journal of Surgery, 2018)
Introduction. Determining the right timing of relaparotomy has always been a challenge and hence a simple objective value is required. Abdominal reoperative predictive index (ARPI) proposed to decide when to reoperate. The study aimed to ascertain whether ARPI could be applied in decision making for relaparotomy at dr.Cipto Mangunkusumo General Hospital (RSCM), Jakarta. Method. A cross sectional study carried out on those underwent relaparotomy in Department of Surgery at RSCM during period of 2009–2015. The follow–up carried out by the residents under supervision of attending surgeons, the laboratory findings were reviewed and tabulated in accordance with clinical variables of ARPI. Eight variables of ARPI were reviewed in these subjects. Results. There were 30 subjects reviewed. In this study there were four frequent variables, i.e. persistent symptoms (for more than 4 days after relaparotomy), abdominal pain (that remains for 48 hours after relaparotomy), surgical site infection (90%), and ileus (70%). Seventy–three–point three percent carried out in more than 7 days after primary operation, while as only 10 percent underwent relaparotomy less than 4 days after primary operation. Conclusion. ARPI is practical guide and may be implemented in helping surgeons to decide relaparotomy should there required. Low compliance lead to delay in the management and associated with high mortality.